Developing the ideal multilingual self in the era of global English: a case in the Japanese context. Issue 3 (4th May 2021) - Takahashi, Chika
ABSTRACT: While there has been a surge of publication on L2 motivation studies, not much has been investigated regarding motivation to learn languages other than English. As a longitudinal interview study, the present study investigated two cases of Japanese university students focusing on the development of ideal L2/L3 self and ideal multilingual self. The results indicated that the development of ideal L2/L3 self was closely related to that of ideal professional self, and an elaborate ideal L2/L3 self helped learners persist and achieve high competence in the target languages. Furthermore, reading skills were considered especially important among the interviewees, which was not emphasised in contexts where learners have daily contact with the target languages. One of the interviewees was not negatively impacted by English and becoming multilingual, which seemed to be helped by a range of factors including ideal L2/L3 self, strong intrinsic motivation, and rich life experiences. The case demonstrated the possibility of developing an ideal multilingual self and becoming multilingual even in an era when English functions as a global language. Based on the results, theoretical and pedagogical implications that might be particularly helpful in foreign language contexts are discussed.